Proses Pembelajaran Pada Anak Berkebutuhan Khusus Tuna Rungu Di SDIP YLPI Pekanbaru - Azzahra, Sabrina; Dea Mustika (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Inclusive education is a place for children with special needs to get the same education without being differentiated. This study aims to describe the learning process and the obstacles experienced by deaf children at SDIP YLPI Pekanbaru in learning. This type of research is qualitative with a case study approach. This study uses interviews, observation and documentation as data collection techniques. The data analysis technique used in this study is according to Miles and Huberman namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the learning process which consists of the planning stage, the implementation stage and the assessment stage for deaf children is not different from other regular children. The planning stage includes the availability of syllabus, lesson plans and PPI for deaf children. The implementation phase consists of opening activities, core activities and closing activities. And the assessment stage given includes attitude assessment, knowledge assessment and skills assessment. In the implementation of learning, several obstacles were encountered, such as limited time to design special plans, difficulty communicating due to language limitations experienced by deaf children and difficulties in giving judgment considerations for deaf children.